2022
DOI: 10.31883/pjfns/145665
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Grape Variety, Yeast and Malolactic Fermentation on Volatile Compounds and Fourier Transform Infrared Spectra in Red Wines

Abstract: Volatile compounds are very important to the flavour and quality of the wine. The study aimed to determine the effect of grape variety (Rondo and Zweigelt), yeast, malolactic fermentation (MLF) and yeast×MLF interaction on the content of volatile compounds in red wines. The wines were produced by sequential inoculation with five commercial yeast strains and a commercial lactic acid bacteria (LAB) strain (induced malolactic fermentation) as well as by inoculation with five commercial yeast strains and without L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 49 publications
(90 reference statements)
2
4
0
Order By: Relevance
“…Wines R1–R5 contained diethyl-2-hydroxybutanedioate (diethyl malate), while R1LAB–5LAB did not contain this compound. Our results regarding the relative content of ethyl lactate in wines subjected to different types of MLF are in agreement with the results of Abrahamse and Bartowsky [ 45 ], Costello et al [ 46 ], Lasik-Kurdyś et al [ 47 ], Malherbe et al [ 48 ] and our previous research [ 38 ]. All these authors state that ethyl lactate is a characteristic volatile product of MLF.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Wines R1–R5 contained diethyl-2-hydroxybutanedioate (diethyl malate), while R1LAB–5LAB did not contain this compound. Our results regarding the relative content of ethyl lactate in wines subjected to different types of MLF are in agreement with the results of Abrahamse and Bartowsky [ 45 ], Costello et al [ 46 ], Lasik-Kurdyś et al [ 47 ], Malherbe et al [ 48 ] and our previous research [ 38 ]. All these authors state that ethyl lactate is a characteristic volatile product of MLF.…”
Section: Resultssupporting
confidence: 93%
“…All these authors state that ethyl lactate is a characteristic volatile product of MLF. Also, the results of the analysis of butyrolactone and 2-phenylethyl acetate conducted in this present study are similar to our previous findings [ 38 ]. In contrast to our study, Abrahamse and Bartowsky [ 45 ] reported that the concentration of 2-phenylethyl acetate was higher in wine subjected to spontaneous MLF compared to induced MLF.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations